Development of Code-Based Chess Board Media to Improve Calculating Abilty in Collection Material - Moch. Faizin; Mohamad Fatih (Edumaspul: Jurnal Pendidikan, 2024)
Numeracy ability is mathematical intelligence which includes the ability to use numbers and calculations, patterns and logic, and a scientific mindset. This increase in numeracy skills can be improved with the help of learning media in the form of a code-based chess board. Innovations in implementing learning using games can be used as a reference for teachers so they can present interesting learning for students. The aim of this research is to determine the stages of development, level of validity and improvement of students' numeracy skills. This research is development research using a modified Borg & Gall development model. This research uses research instruments in the form of interviews, questionnaires, tests (pre-test and post-test) and also documentation. The results of this research show that the validity level of material experts got a score of 86% and the validity level of media experts got a score of 83%. Both validation results show that the media developed by researchers is very feasible and does not require revision. Meanwhile, the increase in students' numeracy skills after using code-based chess media in learning is included in the moderate category.